THE INFLUENCE OF THE BASIC MOTOR ABILITIES ON THE FIVE ATHLETIC DISCIPLINES IN 17- YEAR-OLD STUDENTS - Bejtulla Emini,; Blerim Saiti,; Zorica Stankovska,; Zarko Kostovski, (Sport Scientific And Practical Aspects, 2025)
For the realization of the research, a research procedure was conducted on 250 male students from the fourth year in two municipal high schools, aged 17 to 18 years, with a difference in age of + six months. The subject of the research is the basic motor space in students, as a predictor system and their impact on the five athletic disciplines that are an integral part of the program in the competition system of the Federation of School Sports as a criterion system of variables. By applying the Multiple Regression Analysis, the influences of the predictors on each of the criterion variables were determine